Associations between body mass index and episodic memory for recent eating, mindful eating, and cognitive distraction: A cross‐sectional study - Elanor C. Hinton; Victoria Beesley; Sam D. Leary; Danielle Ferriday (Wiley, 2024)
Abstract Objectives Eating while distracted has been associated with a higher body mass index (BMI), whereas mindful eating and episodic memory for recent eating have shown the opposite pattern. This pre‐registered, global study (https://osf.io/rdjzk) compared the relative association between these variables (and four "positive controls": restraint, disinhibition, emotional eating, plate clearing) and self‐reported BMI. The timing of data collection (April-May 2020) during the SARS‐CoV‐2 pandemic enabled an investigation of the impact of stay‐at‐home restrictions imposed on the UK population on the measures of eating behavior. Methods An online survey was completed, including: (i) demographic data (e.g., self‐reported BMI), (ii) Likert ratings assessing episodic memory for recent eating, mindful eating, cognitive distraction, restrained eating, emotional eating, disinhibition and plate clearing over the last 12 months and the last 7 days (during the first UK COVID‐19 lockdown), and (iii) the Mindful Eating Questionnaire (MEQ). Results A large adult sample participated (N = 846; mean (SD) age = 33.0 (14.3) years; mean (SD) BMI = 24.6 (5.6) kg/m2). Mindful eating (MEQ‐total score) was associated with a lower self‐reported BMI (β = −0.12; 95% CI = −0.20, −0.04; p = 0.004), whereas disinhibited eating was associated with a higher self‐reported BMI (β = 0.30; 95% CI = 0.21, 0.38; p < 0.001). In UK participants (n = 520), consistent changes in eating behavior during lockdown were not found. For those that did experience change, decreases were reported in; emotional eating, disinhibited eating, focusing on taste during a meal (a measure of mindful eating), and using a smart phone while eating. Conclusions These findings provide evidence in a large global sample for associations between BMI and (i) mindful eating, and (ii) disinhibited eating. Future research should evaluate whether mindful eating demonstrates a prospective association with body weight and should consider mechanisms of action.